Estratégia alimentar com ciclos de restrição e realimentação no desempenho produtivo de juvenis de tilápia do Nilo da linhagem GIFT - da Palma, Eduardo Henrique [UNESP]; Takahashi, Leonardo Susumu [UNESP]; Dias, Luciana Thie Seki; Gimbo, Rodrigo Yukihiro [UNESP]; Kojima, Juliana Tomomi [UNESP]; Nicodemo, Daniel [UNESP] (My University, 2010)
The objective of this study was to evaluate the occurrence of compensatory answer on productive performance of Nile tilapia Oreochromis niloticus juveniles, GIFT line, submitted to different feeding strategies. It was used 135 juveniles tilapias distributed in nine 100L polyethylene tanks each. The tested strategies were the control group (fed everyday), group fed for 5 days followed by 2 days of food restriction (5A/ 2R) and group fed for 4 days followed by 3 days of food restriction (4A/3R). Were evaluated physical chemical water parameters e growth performance. Results were submitted to an analysis of variance and averages compared by Tukey test 5%. Water quality, condition factor and feed conversion were not influenced by feeding strategy. Group fed 5A/2R strategy showed final weight, weight gain and specific growth rate similar to group continually fed (7.8 e 9.2g; 6.4 e 7.8g e 2.7 e 3.0% day-1, for final weight, weight gain and specific growth rate, respectively). The strategy 4A/3R showed the poorest productive performance. Strategy 5A/2R can be used in Nile tilapia juveniles feeding without damage to the fish productive performance, allowing a reduction of up to 22.5% on the feed quantity offered.
Feeding strategies with cycles of restriction and refeeding on growth performance of Nile tilapia juveniles, GIFT line
Keywords: Feeding strategy; Food deprivation; Oreochromis niloticus